The THE INFLUENCE OF KOREAN POPULAR CULTURE TOWARDS THE INTENTION TO VISIT SOUTH KOREA (Survey on Student’s in Sam Ratulangi University Manado) - Falencia Wullur; Frederik G. Worang; Ferdinand J. Tumewu (Universitas Sam Ratulangi, 2023)
The popularity of Korean culture around the world has made people affected by this culture. This Korean culture well known as Korean Wave or Hallyu phenomena cover various aspects such as drama, music, fashion, make-up and etc. Korean Wave or Hallyu is a term to describe South Korean pop culture that has been successfully exported across the globe, including Indonesia specifically in Manado City. The objectives of this study are to determine the students in Sam Ratulangi University Manado perceive South Korean images as a Potential tourist destination that is seen in Korean Pop, Korean dramas, and Korean Food could lead to the intention to visit South Korea in the future. The research respondents were 108 respondents. Questionnaire distribution is carried out online using Google Form. The method that researchers use in this study is a quantitative method. The data analysis method used was multiple linear regression analysis using SPSS as a data processing tool. The results from research data on the influence of the Korean Wave on the South Korean tourism sector, researchers found that Korean wave (K–Pop, K–Drama, K–Food) influence the students intention to make South Korea as a Potential Tourist Destination. In other words Korean Wave can affect the South Korea tourism sector. Keywords: korean pop, korean drama, korean food, south korea, intention to visit